2015
DOI: 10.1039/c5ra00589b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of host–guest UV-blocking materials by intercalation of fluorescent anions into layered double hydroxides

Abstract: Materials for blocking UV light play important roles in a variety of areas such as protecting the human skin and increasing the lifetime of polymers. In this work, a new type of host-guest UV-blocking material has been synthesized by the introduction of a fluorescent anion, 2-[2-[4-[2-(4-carboxyphenyl)vinyl]phenyl]vinyl]benzoate (CPBA), into the interlayer galleries of a ZnAl-NO 3 layered double hydroxide (LDH) precursor by an anion-exchange method. The structure and the thermal and photostability of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 36 publications
1
37
0
2
Order By: Relevance
“…26 Previous studies have reported that LDH can inhibit the photo-oxidation of asphalt during weathering, especially at high loading levels. 28 For example, Wang et al 29 have developed several organic UVAs-intercalated LDH systems, which signicantly enhance the stability of polypropylene during UV weathering. 28 For example, Wang et al 29 have developed several organic UVAs-intercalated LDH systems, which signicantly enhance the stability of polypropylene during UV weathering.…”
Section: Introductionmentioning
confidence: 99%
“…26 Previous studies have reported that LDH can inhibit the photo-oxidation of asphalt during weathering, especially at high loading levels. 28 For example, Wang et al 29 have developed several organic UVAs-intercalated LDH systems, which signicantly enhance the stability of polypropylene during UV weathering. 28 For example, Wang et al 29 have developed several organic UVAs-intercalated LDH systems, which signicantly enhance the stability of polypropylene during UV weathering.…”
Section: Introductionmentioning
confidence: 99%
“…After the ion‐exchange interaction of SA into the interlayer galleries of LDH, the three peaks mentioned above appeared at 2θ = 7.03° (003), 16.44° (006), and 17.16° (009), respectively. The corresponding interlayer distance d (003) was expanded to 1.260 nm, indicating that SA anions have successfully replaced NO3 in the interlayer galleries to form LDH‐SA . As commonly observed in the intercalation of large anions into LDH, the two reflections at (015) and (018) merged and broadened in the pattern of LDH‐SA, which might be related to a partial loss of crystallinity or turbostratic disorder .…”
Section: Resultsmentioning
confidence: 75%
“…The band around 3425 cm −1 shown in the spectrum of LDH was assigned to the stretching vibration of the hydroxyl groups of LDH layers and interlayer water molecules . The sharp band observed at 1364 cm −1 corresponded to the ν 3 stretching vibration of NO3 group, while the band at 450 cm −1 was the signal of OMO vibrations in the LDH layers . The spectrum of SA exhibited several distinctive bands, for example, the absorbance at 3490 cm −1 from the aromatic COH, 1670 and 1376 cm −1 from the vibration of COO − , 1175 and 1040 cm −1 from the characteristic absorption band of SO3.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations